CO2 methanation in the presence of methane: Catalysts design and effect of methane concentration in the reaction mixture. Issue 1 (February 2020) - Pastor-Pérez, L.; Patel, V.; Le Saché, E.; Reina, T.R.
Abstract: The work in this paper evidences the viability of producing synthetic natural gas (SNG) via the methanation reaction tackling two fundamental challenges on methanation catalysis (i) the development of advanced catalysts able to achieve high CO2 conversion and high methane yields and (ii) the unexplored effect of residual methane on the methanation stream. Both challenges have been successfully addressed using Ni/CeO2 -ZrO2 catalysts promoted with Mn and Co. Mn does not seem to be a good promoter while Co prevents carbon deposition and secondary reactions. In fact, our Co-doped sample reached high levels of CO2 conversion and CH4 selectivity, especially at low reaction temperatures. In addition, this catalyst exhibits excellent catalytic behaviour when methane is introduced into the gas mixture, indicating its feasibility for further study to be conducted in realistic flue gases environments and methanation units with recycling loops. Furthermore, when methane is introduced in the reactant mixture, the Ni-Co/CeO2 -ZrO2 sample is very stable maintaining high levels of conversion and selectivity. Overall our Co-doped catalyst can deliver high purity synthetic natural gas for long-term runs, promising results for gas-phase CO2 conversion units. Highlights: Synthetic natural gas production over highly effective bimetallic Ni-Co catalysts. First report on CO2 methanation in the presence of methane. Chemical CO2 recycling via CO2 methanation. Design of methanation units with recycling loops.